Growth model in crossbred dairy calves on grazing with protein-energy-mineral supplementation - Viamonte Garcés, María I.; Acosta Iglesias, D.; Calva Moreno, F.A.; Naula Campoverde, D.J. (Cuban Journal of Agricultural Science, 2024)
The research was conducted from March to May 2020 to develop functions to estimate growth and increase in live weight and average daily gain in dairy cattle in pre-fattening stage, in rotational grazing, with grasses association and protein-energy-mineral supplementation. Information was taken from the botanical composition in percentage, fresh and dry matter in a hectare divided into four equal plots, the chemical composition of the grasses association and the cattle stocking rates capacity of the system, live weights and weight gains in the animals. From this information, functions were developed to estimate growth and increase in live weight and average daily gain in crossbred dairy calves until their future productive performance. The grazing area consisted of 51.51 % plant biomass of ratana grass (Ischaemum indicum) and 20.74 % forage peanut (Arachis pintoi). The quality of the grasses association with the highest contributions of crude protein was in forage peanut and ratana (20.75 and 23.44 %, respectively). The average gross energy contributions were 1023.9 kJ/kgDM, with the best values ​​for forage peanut (1107.24 kJ/kgDM). The total grass yield was 3488.50 kg/ha. The prediction of future productive performance in fattening was influenced by weight increases in the first three months of age of the calves, regardless of birth weight. These changes in the growth curve are due to the diet with energy-protein-mineral supplementation.